Sketching the product strategy: team processes in early design innovation. (30th October 2007) - Lauche, Kristina
The early stages of product innovation can crucially influence the success and direction of any product. Yet they tend to be fuzzy, highly politicised and notoriously under-researched. This paper explores the characteristics of early design stages based on extensive field observations in two case studies. Both teams not only attempted to innovate radically their product, but also had to re-think the strategy and the organisation. The analysis of video recordings, artefacts and interviews showed that the key challenges were to integrate the demands and different innovation potentials into a coherent concept and to coordinate team activities and negotiate resources. Later, these secondary tasks of design innovation were often perceived as a burden by the designers, but turned out to be of crucial importance for the success of the project.